2008
DOI: 10.1099/vir.0.2008/004150-0
|View full text |Cite
|
Sign up to set email alerts
|

Histidine at codon 154 of the prion protein gene is a risk factor for Nor98 scrapie in goats

Abstract: Prion protein gene (PRNP) polymorphisms are involved in modulating the appearance of atypical/Nor98 scrapie in sheep, with the alleles AHQ and AF141RQ strongly associated with occurrence of the disease. The presence of histidine at codon 154 has also been detected in Nor98-affected goats, but statistical analysis of the association between Nor98 and goat PRNP polymorphisms has not been reported previously. Here, a case–control study was carried out on eight Nor98-positive goats and 246 negative herdmates belon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 27 publications
1
56
0
2
Order By: Relevance
“…A doença pode apresentar-se na forma clássica em ovinos e caprinos geneticamente susceptíveis (AVMA 2002, Goldmann & Baylis 2004, González et al 2009, OIE 2009) e na forma atípica, diagnosticada na Noruega, por Benestad et al (2003), denominada "Nor98", posteriormente observada em outras partes do mundo (Arsac et al 2007,Cosseddu 2007, Jeffrey & González 2007, Seuberlich et al 2007, Colussi et al 2008, Fediaevsky et al 2008, Loiacono et al 2009, Martinez 2010 (Fernandes et al 1978), mas a primeira notiϐicação oϐicial à Organização Mundial de Saúde Animal (OIE) foi de um surto, também no RS, ocorrido em 1985, (Pereira 1996). Posteriormente, entre 1995 e 2010, foram registrados surtos, no RS, Paraná (PR), Mato Grosso do Sul (MS), Mato Grosso (MT), Minas Gerais (MG) e São Paulo (SP) (OIE 2011a).…”
Section: Introductionunclassified
“…A doença pode apresentar-se na forma clássica em ovinos e caprinos geneticamente susceptíveis (AVMA 2002, Goldmann & Baylis 2004, González et al 2009, OIE 2009) e na forma atípica, diagnosticada na Noruega, por Benestad et al (2003), denominada "Nor98", posteriormente observada em outras partes do mundo (Arsac et al 2007,Cosseddu 2007, Jeffrey & González 2007, Seuberlich et al 2007, Colussi et al 2008, Fediaevsky et al 2008, Loiacono et al 2009, Martinez 2010 (Fernandes et al 1978), mas a primeira notiϐicação oϐicial à Organização Mundial de Saúde Animal (OIE) foi de um surto, também no RS, ocorrido em 1985, (Pereira 1996). Posteriormente, entre 1995 e 2010, foram registrados surtos, no RS, Paraná (PR), Mato Grosso do Sul (MS), Mato Grosso (MT), Minas Gerais (MG) e São Paulo (SP) (OIE 2011a).…”
Section: Introductionunclassified
“…Later studies conducted on archived tissue specimens revealed that atypical scrapie is not a new disease and has been existed at least from late 1980s in the UK herds [98,99]. In the following years, many atypical scrapie cases were reported in sheep and/or goats from [100][101][102][103], North America [104] and New Zealand [105], as well.…”
Section: Atypical Scrapie In Sheep and Goatsmentioning
confidence: 99%
“…Although there is very limited data about relationship atypical scrapie and PRNP genotypes in goats, it has been reported that the presence of histidine at codon 154 may associated with atypical cases in goats, as well [103,109].…”
Section: Atypical Scrapie In Sheep and Goatsmentioning
confidence: 99%
“…In Italian goats, different SNPs were found at codons G/V 37 , T/P 110 , G/S 127 , L/Q 133 , M/I 137 , I/M 142 and T 142 , H/R 143 , R/H 151 , R/H 154 , P/Q 168 , T/P 194 , R/Q 211 , Q/K 222 and S/P 240 (Colussi et al, 2010). Moreover, in an Italian case-control study, the H154 variation in goats was statistically associated with Nor98 (Colussi et al, 2008). In Greece and Cyprus, goats represent one of the largest populations in Europe; in these countries, several scrapie cases have been registered (European Commission, 2012).…”
Section: Role Of Prnp In Small Ruminantsmentioning
confidence: 99%
“…The onset of clinical signs in atypical scrapie is characterised by ataxia, with lack of coordination and itching (Colussi et al, 2009). Goats affected by classical scrapie are between 2 and 5 years old, whereas goats affected by atypical scrapie are usually 6 years old or older (Colussi et al, 2008). However, there are variations in the clinical symptoms between individual animals or between animals of different breeds, and these variations are always influenced by the prion strain and the animal's genotype (Gavier-Widén et al, 2005;Radostits et al, 2007).…”
Section: Introductionmentioning
confidence: 99%